Characteristics and Outcome of 588 Children with Myelomeningocele at a Tertiary Childcare Hospital of S. Punjab, Pakistan - Shakeel Ahmed, Shoaib Saleem Khan, Ubaid Ullah, Waqas Noor Chughtai, Malik Liaqat Ali Jalal, Kashif Chishti (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To describe characteristics and outcome of children with myelomeningocele at a tertiary childcare hospital of South Punjab, Pakistan. Study Design: A retrospective study. Place and Duration of the Study: Department of Pediatric Neurosurgery, The Children’s Hospital and Institute of Child Health, Multan Pakistan from January 2019 to December 2021. Material and Methods: Data of a total of 588 children of either gender aged up to 12 years undergoing myelomeningocele repair during the 3 year study period were analyzed. Gender, age and residential status of all children were recorded. Diagnosis of MMC was confirmed with the help of medical history, clinical findings and radiological investigations like magnetic resonance imaging (MRI). All patients underwent standard management protocols. Results: In a total of 588 children with MMC, 359 (61.1%) were boys and 229 (38.9%) girls. Overall, mean age was calculated to be 6.29±6.51 months ranging from 1 day to 7 years while 409 (69.6%) children were aged between 1 to 6 months. Residential status of 427 (72.6%) children was rural. Lumbosacral was the most commonly affected region noted in 440 (74.8%) children. No intra-operative or immediate post-operative mortality was noted among children with MMC. Conclusion: Most of the children with myelomeningocele were boys and aged between 1 to 6 months. Lumbosacral region was the most frequently affected region. Excellent intra-operative or immediate post-operative outcomes of MMC repair were reported.